Genome-wide association studies on charcoal rot resistance in soybean (Glycine max, L.): Genome-wide association studies on charcoal rot resistance in soybean (Glycine max, L.) - VENNAMPALLY NATARAJ; PAWAN KUMAR AMRATE; MILIND B RATNAPARKHE; SHIVAKUMAR MARANNA; LAXMAN SINGH RAJPUT; GIRIRAJ KUMAWAT; NISHA AGRAWAL; SALIKRAM MOHARE; MANOJ SRIVASTAVA; K BHOJARAJA NAIK; RISHIRAJ SINGH RAGHUVANSHI; SANJAY GUPTA (Journal of Oilseeds Research, 2023)
A genome-wide association study (GWAS) was conducted for Charcoal rot resistance by using 267 soybean germplasm lines. GWAS analysis revealed two most significant SNPs at chromosome 3 (S3_8215775 and S3_8309181) for multiple traits associated with adult plant resistance. Candidate genes related to calcium ion signaling, response to nematode infestation, abscisic acid stimulus and defense response to bacteria were identified within the flanking regions of the significant SNP positions. Among all, one most important gene (Glyma.03G057100) involved in jasmonic acid biosynthesis was identified. Two SNPs each on chromosome 8 (S8_22467783 and S8_22467802) and chromosome 9 (S9_2923863 and S9_2935518), associated with seedling resistance have also been identified.